Ocorrência de ácaros Calamicolas em Psittaciformes de origem brasileira: observações preliminares - Cassius Catao Gomes Jardim (1992)
It was studied primary and secundary feather of 170 brasilian Psittaciformes (Aves) caged in Belo Horizonte and Espírito Santo State (ES). The quills was cuted longitudinaly and their contents examined under stereoscopic microscopic for search of mites. It was founded mites of four families: Syringobilidae, Syringophilidae, Pyrogliphidae and Dermogliphidae. The genus most frequently founded was Paralgopsis, folowed by Cystoidosoma. Mites of the families Syringophilidae and Dermoglyphidae was founded sporadically. Greatest percentage of infestation was founded in Serra (ES), at the Centro de Preservação dos Psitacídeos do Espírito Santo e Sul da Bahia (CEPPESBA),(62,5% of examined birds). In Meaipe, ES , at the Criatório Augusto Ruschi, it was founded 40% of infestation, and at the BHZOO, in Belo Horizonte , 21.5% of the examined birds was infested. Lesions was observed within infested feather. This lesion was associated with mites species that probabily caused them. Parts of mites of the genus Paralgops was observed within mites of the genus Cystoidosona.